2004
DOI: 10.1590/s1516-89132004000600002
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum sp . inoculation in wheat, barley and oats seeds greenhouse experiments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 38 publications
1
7
0
3
Order By: Relevance
“…Treatments using doses of 100% of nitrogen demanded by the crop, associated to the bacteria, generated an increase of 9% in the production, in relation to the dose of 100% of N without the bacteria (DALLA SANTA et al, 2004), being these data similar to the found by REYNDERS and VLASSAK (1982), where the use of the strains S631 and SpBr14 added an increase of 9.14% and 14.82%, respectively, in the agricultural yield. DIDONET et al (1996) in their studies, concluded that the use of inoculants in the form of strains of peat moss powder JA04 with 15 kg ha -1 of N in the wheat sowing, completely substitutes the nitrogen fertilizer of 15 kg ha -1 of N in the sowing and 45 kg ha -1 in cover, without the use of the diazotrophic bacteria.…”
Section: Efficiency In Yieldsupporting
confidence: 70%
“…Treatments using doses of 100% of nitrogen demanded by the crop, associated to the bacteria, generated an increase of 9% in the production, in relation to the dose of 100% of N without the bacteria (DALLA SANTA et al, 2004), being these data similar to the found by REYNDERS and VLASSAK (1982), where the use of the strains S631 and SpBr14 added an increase of 9.14% and 14.82%, respectively, in the agricultural yield. DIDONET et al (1996) in their studies, concluded that the use of inoculants in the form of strains of peat moss powder JA04 with 15 kg ha -1 of N in the wheat sowing, completely substitutes the nitrogen fertilizer of 15 kg ha -1 of N in the sowing and 45 kg ha -1 in cover, without the use of the diazotrophic bacteria.…”
Section: Efficiency In Yieldsupporting
confidence: 70%
“…The benefits of inoculation of cereal crops with diazotrophic bacteria have been reported in other studies as well (DALLA SANTA et al, 2004;SALA et al, 2008). Hungria et al (2010) found that the use of A. brasilense in corn resulted in a 30% increase in productivity, corresponding to 823 kg ha -1 , compared to control without inoculation.…”
Section: Introductionmentioning
confidence: 53%
“…Zambre et al (1984) também obtiveram o máximo de aumento na produtividade de grãos, em experimento de campo, com plantas de trigo que receberam 120 kg ha -1 de N, e outros trabalhos relatam aumentos com a adição de 100 % do N recomendado para a cultura (Reynders & Vlassak, 1982;Millet & Feldman, 1984;Dalla Santa et al, 2004). O aumento da produtividade na maior dose de N também poderia ser atribuído a uma possível seleção natural e, ou, uma adaptação na associação planta-bactéria diazotrófica, uma vez que o isolado de A. insolitus foi obtido de plantas de trigo na presença de adubação nitrogenada (Sala et al, 2005).…”
Section: Discussionunclassified
“…Existem muitos relatos de respostas positivas da inoculação de bactérias diazotróficas associadas à cultura do trigo (Dalla Santa et al, 2004;Roesch et al, 2005), havendo, entretanto, outros relatos em que não houve efeito da inoculação (Ogüt et al, 2005). Mertens & Hess (1984), utilizando uma estirpe de Azospirillum em três anos de experimento de campo, obtiveram aumento na produtividade de grãos, que variou de 8 a 32 %, variação ocorrida entre os anos e dentro do mesmo ano de cultivo.…”
Section: Introductionunclassified